Dispersion modelling in rivers for water sources protection: a case study - Duarte, António A. L. Sampaio (1999)
Judicious selection of mathematical models for application in a specific river basin management can mitigate prediction uncertainty. Therefore, intervention times will be established with better reliability and alarm systems could efficiently protect the aquatic ecosystems. Parameters estimation for the in situ dispersion river water behaviour characterisation and performance evaluation of different numerical techniques when applied to river water dispersion modelling were the main purposes of this research work. A monitoring program was carried out using tracer injection (rhodamine WT) to assess the environmental impact of Urgeiriça mining waters in a Mondego river reach, between Caldas da Felgueira and Aguieira reservoir, where the Seara abstraction point is located. This paper describes the methodology used in the tracer experiments, the results of different simulation models and the performance of two different numerical methods. For flow discharge values of 40 and 140 m3s-1, longitudinal dispersion coefficients average values are 35 and 60 m2s-1. The recovered rhodamine mass ranges from 55 to 65% of the total injected mass at all sampling sites. The application of DUFLOW model, that simultaneously solves hydrodynamics and water quality, showed the best agreement with experimental data, allowing a reasonable support for impact assessment of different discharges scenarios in the river water quality.